2021
DOI: 10.18844/cjes.v16i3.5769
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of advance organiser learning model assisted by Zoom Meeting application

Abstract: The COVID-19 pandemic caused the education system to suddenly move from offline to online learning, so it takes a variety of effective learning design trials. This research aims to find out the effectiveness of the advance organiser learning model assisted by the Zoom Meeting application. This research was conducted at State Junior High School 3 Binamu, Jeneponto Regency. The research sample was 20 people. The research was conducted with an embedded design model of mixed methods. The findings show that the onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Video conferencing platforms (e.g., Zoom) and engaging materials (e.g., videos and songs) can be helpful in increasing online collaboration and interactions between students and teachers (Alves et al, 2021;Souheyla, 2021). While greater teacher presence, more effective content delivery (Prijambodo & Lie, 2021), and improved quality of internet connection and distance-learning facilities (Syaharuddina et al, 2021) facilitate online learning and help students become more "successful learners" (Serhan, 2020), most students had lower participation and fewer interactions through Zoom than in a traditional classroom. Moreover, most reported that they would be more comfortable in traditional classroom settings (Abbasi et al, 2020;Lieberman, 2020;Serhan, 2020).…”
Section: Lessons From Online Educationmentioning
confidence: 99%
“…Video conferencing platforms (e.g., Zoom) and engaging materials (e.g., videos and songs) can be helpful in increasing online collaboration and interactions between students and teachers (Alves et al, 2021;Souheyla, 2021). While greater teacher presence, more effective content delivery (Prijambodo & Lie, 2021), and improved quality of internet connection and distance-learning facilities (Syaharuddina et al, 2021) facilitate online learning and help students become more "successful learners" (Serhan, 2020), most students had lower participation and fewer interactions through Zoom than in a traditional classroom. Moreover, most reported that they would be more comfortable in traditional classroom settings (Abbasi et al, 2020;Lieberman, 2020;Serhan, 2020).…”
Section: Lessons From Online Educationmentioning
confidence: 99%
“…Hal ini menjadi polemik di masyarakat dengan memunculkan perdepatan di dunia pendidikan, khususnya di masyarakat. Penyebabnya adalah sistem pendidikan di Indonesia cenderung mengutamakan pembelajaran tatap muka (luring), sehingga ketersediaan sarana dan prasarana pembelajaran online (daring) juga masih terbatas (Syaharuddin et al, 2021). Selain itu ketidaksiapan siswa, guru dan orang tua berperan untuk membelajarkan anak didiknya secara daring di lingkungan rumahnya.…”
Section: Pendahuluanunclassified
“…(Wardhani, 2022) said that the lecturer used google meet to have straight communication or two ways learning with the students and it could be applied using Zoom Cloud Meeting. Another finding by (Syaharuddin et al, 2021) said that the online advance organizes learning model used an effective Zoom Cloud Meeting. They were (1) the application of advance organizer learning had a positive relationship with student learning outcomes;…”
Section: Introductionmentioning
confidence: 99%